A review of the challenges and application of public-private partnership model in Chinese garbage disposal industry. (1st September 2019) - Wang, Ling; Yan, Dongyi; Xiong, Yan; Zhou, Lihong
Abstract: With the rapid development of economy and the increase of population in China, the phenomenon of "Garbage Siege" has severely damaged the city image of Chinese cities and threatened the inhabitant both in physical and mental health. Garbage disposal has become an urgent matter to deal with for governments at all levels. Since 2013 the central government of China has widely promoted public-private partnership (PPP) model to improve the efficiency of garbage disposal services, and the number of garbage disposal PPP projects has also increased. According to the data released by the Ministry of Financial of the People's Republic of China (MOF), a total of 198 projects with 59.1 × 10ˆ9 yuan RMB have already applied the PPP model in garbage disposal industry. This paper introduces the development situation of the PPP model in the garbage disposal industry from the aspects of specific model selection, return mechanism and signing rate. Some possible risks and challenges of the PPP model in the garbage disposal industry are manifested through the case study and data analysis. Finally, a guide and some suggestions are put forward from the financing channels, the government reputation and the applicability of the PPPs. Highlights: PPP model is widely used in garbage disposal industry, and has regionally differentiated distribution characteristics. China's garbage disposal PPP projects are faced with risks brought by the government, social investment and other parties. Financing risks, the lack of experience and the pseudo-PPP projects occurred in promoting garbage disposal PPP projects. Some suggestions are presented for standardizing the operation of garbage disposal PPP projects.